Diversity of Bird Species in Bagek Kembar Sekotong Area - Safariyanti Manisa; Sri Aprilia Nur Larasati; Ramdani Kurniawan; Putu Linda Agustini; Dian Dwi Permatasari; Rena Purnamawati; Hasita Pebrianti; Lia Umami; Harsa Nanik (Journal of Biology, Environment, and Edu-Tourism, 2025)
This study aims to assess bird species diversity in the Bagek Kembar Ecotourism Area, Sekotong District, West Lombok Regency. The background of this research is based on the importance of biodiversity information as a foundation for conservation efforts and sustainable ecotourism area management. Observations were conducted over three days in April 2023 using the point count method across three habitat types: fishponds, mangroves, and coastal areas, encompassing nine observation plots. The results revealed the presence of 39 identified bird species in the area. The Shannon-Wiener diversity index (H') value was 2.87, indicating a moderate level of diversity (1 < H' < 3). However, the dominance of the Cerulean Kingfisher (Alcedo coerulescens) indicates an uneven distribution of individuals among species, which may reflect ecological pressure. The Bagek Kembar Ecotourism Area has a reasonably good potential for bird diversity, yet future management should consider species distribution and possible environmental stressors. Regular monitoring and the development of habitat-based conservation strategies are recommended to maintain ecosystem stability and biodiversity in the area.